2018
DOI: 10.1016/j.amepre.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Rape-Related Pregnancy and Association With Reproductive Coercion in the U.S.

Abstract: Introduction: Rape-related pregnancy is a public health problem where sexual violence and reproductive health intersect; yet, there is a dearth of research to inform public health practice. The authors examined the prevalence and characteristics of rape-related pregnancy in U.S. women and its association with intimate partner reproductive coercion. Methods: Data years 2010–2012 are pooled from the National Intimate Partner and Sexual Violence Survey, a telephone survey of U.S. adults. Accounting for complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
(50 reference statements)
5
42
0
Order By: Relevance
“…17 Data from a study of a convenience sample of females ( n= 148) seeking a protection order from an intimate partner reported the outcome of IPV rape-related pregnancies ( n= 32; i. e., 81% live birth, 16% abortion, 3% still born). 16 Unit costs were estimated payments for medical treatment for medically assisted abortion, 19 pregnancy and delivery, 18 and stillborn hospital birth 20 applied to the estimated number of female IPV vaginal rape victims in 2012 NISVS1, 1,16,17,46 (i.e., cost of child-rearing not included; Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…17 Data from a study of a convenience sample of females ( n= 148) seeking a protection order from an intimate partner reported the outcome of IPV rape-related pregnancies ( n= 32; i. e., 81% live birth, 16% abortion, 3% still born). 16 Unit costs were estimated payments for medical treatment for medically assisted abortion, 19 pregnancy and delivery, 18 and stillborn hospital birth 20 applied to the estimated number of female IPV vaginal rape victims in 2012 NISVS1, 1,16,17,46 (i.e., cost of child-rearing not included; Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that 1.2% of women are raped annually in the United States, and almost one in five women over 18 are the victims of attempted or completed rape in their lifetimes (Basile et al. ). In their examination of data from the 2010–2012 National Intimate Partner and Sexual Violence Survey, Basile et al also found that 2.4%—or almost 2.9 million women—experienced rape‐related pregnancy during their lifetime; among these women, over 77% have reported the perpetrator being a current or former intimate partner.…”
Section: Discussionmentioning
confidence: 99%
“…In their examination of data from the 2010–2012 National Intimate Partner and Sexual Violence Survey, Basile et al also found that 2.4%—or almost 2.9 million women—experienced rape‐related pregnancy during their lifetime; among these women, over 77% have reported the perpetrator being a current or former intimate partner. Of women who were vaginally raped by an intimate partner, 30% experienced reproductive coercion by that partner (either by trying to get her pregnant, stopping her from using birth control, or refusing to use a condom; Basile et al., ). This poses a particular threat to the reproductive health of girls and women, limiting their ability to make choices about pregnancies and parent their children in safe environments.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive coercion (RC) is defined as controlling behaviors by male partners or family members to reduce women's and girls' reproductive autonomy [13] in the forms of limiting her access to or use of contraceptive methods, coercion to become pregnant against her will, and control of decisions to maintain or terminate a pregnancy [14]. A growing body of evidence demonstrates that RC is independently associated with unintended pregnancy, beyond the effects seen for IPV alone [2,11,15,16], lending support to the hypothesis that this understudied form of GBV is a mechanistic link explaining, at least in part, the consistently-demonstrated associations between IPV and poor SRH outcomes [11]. While research describing the burden of RC in LMIC contexts is still at its inception, initial studies confirm the high prevalence of RC (as perpetrated by both male partners and in-laws) and its connection to experiences of unintended pregnancy [17] an association which has been previously demonstrated in the United States [2,8,11].…”
Section: Introductionmentioning
confidence: 99%